Alternative treatment of polycystic ovary syndrome: pre-clinical and clinical basis for using plant-based drugs - Malik, Sidra; Saeed, Saira; Saleem, Ammara; Khan, Muhammad Imran; Khan, Aslam; Akhtar, Muhammad Furqan (Frontiers in Endocrinology, 2024)
The most common cause of infertility and metabolic problems among women of reproductive age is polycystic ovary syndrome (PCOS), a multifaceted disorder. It is an endocrine disorder that occurs in approximately one in seven women. Among these PCOS patients, two thirds will not ovulate on a regular basis and seek treatment for ovulation induction. The symptoms vary in their severity, namely ovulation disorders, excessive androgen levels, or polycystic ovarian morphology. All these symptoms require a therapeutic approach. Many drugs are used to eradicate PCOS symptoms, like metformin, clomiphene citrate, spironolactone, and pioglitazone. Long-term treatment is required to achieve the desired outcome, which is often accompanied by significant adverse reactions. Some herbs and phytochemicals are equally effective for treating PCOS and produce minimal side effects. Recently, herbal products are gaining popularity due to their wide biological activities, safety, availability, and efficacy. The present review covers aetiology, current treatment, pathophysiology, and detailed pre-clinical and clinical studies on plants and phytochemicals that are proven to be useful for the treatment of symptoms associated with PCOS.